EXTRACTION OF VINORELBINE FROM LEAVES OF CATHARANTHUS ROSEUS AND ITS APPLICATION IN TREATING BREAST CANCER USING IN VIVO MOUSE MODELS - GIREESH KAMATH. H; DEECARAMAN; RAMESH KV (International Journal of Pharma and Bio Sciences, 2016)
Extracts from the leaves of Catharanthus roseus were collected using methanol. Three individual alkaloids were fruitfully separated by TLC, purified using column chromatography and one of them was successfully identified as vinorelbine. Nude mice xenografted with breast cancer cell line MDAMB231 were treated through vinorelbine (30 mg/kg body weight, i.p.). Mice responded to the treatment and showed a significant decrease in the tumor volume in comparison to mice of the control growth. Results shows that the plant extracted vinorelbine may be helpful for treating the breast cancer.